2003
DOI: 10.1076/orbi.22.3.177.15617
|View full text |Cite
|
Sign up to set email alerts
|

Use of inhaled nitrous oxide for minor eyelid surgery: A placebo-controlled study

Abstract: Entonox has been used effectively in different specialties for pain relief. However, our study was unable to show this beneficial effect in relieving pain from local anaesthetic injections for minor eyelid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A mixture of inhaled nitrous oxide and oxygen in equal proportions (Entonox) is an effective, short acting analgesic with few side effects that is widely used in obstetrics departments but which has also been used prior to a variety of minor surgical procedures (Bhatt et al, 2003;McIntyre, Dixon & Pantelides, 2003). We therefore prospectively evaluated the use of Entonox as an analgesic agent for patients undergoing BMAB.…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of inhaled nitrous oxide and oxygen in equal proportions (Entonox) is an effective, short acting analgesic with few side effects that is widely used in obstetrics departments but which has also been used prior to a variety of minor surgical procedures (Bhatt et al, 2003;McIntyre, Dixon & Pantelides, 2003). We therefore prospectively evaluated the use of Entonox as an analgesic agent for patients undergoing BMAB.…”
Section: Introductionmentioning
confidence: 99%
“…, N 2 O was utilized during the injection of lidocaine into the eyelid. Their placebo control study showed no significant difference in pain and an increase in complications with N 2 O 33 …”
Section: Resultsmentioning
confidence: 95%
“…Their placebo control study showed no significant difference in pain and an increase in complications with N 2 O. 33 In hysteroscopy, N 2 O has been perceived to be dangerous when used as the distending agent, 34,35 but has recently been evaluated in small studies as an anesthetic agent. Hong et al .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…She would likely be best treated under local anesthesia with sedation, not just nitrous oxide (Level II Evidence 43 ), or general anesthesia with upper lid blepharoplasty with skin excision and conservative muscle and fat management. Skin closure could be with sutures or glue (Level II Evidence 50 ).…”
Section: Suggested Treatment For Clinical Scenariomentioning
confidence: 99%
“…42 A prospective randomized controlled trial of nitrous oxide versus air for eyelid surgery by Bhatt et al showed no difference in diminishing the pain of injection of local anesthetics but did find more side effects in the nitrous oxide group (Level II Evidence). 43 In a 2009 double-blinded study in which lidocaine was injected in one eyelid and articaine was injected into the other eyelid, 22 of 30 patients found the articaine to be less painful (Level II Evidence). 44 Although it is more expensive, articaine has a safety profile similar to lidocaine.…”
Section: Evidence On Pain Managementmentioning
confidence: 99%